Unlocking Creative Potential: The Impact of Sasambo Wisdom on Narrative Writing Skills - Saputri, Ria; Mulyati, Yeti; Sumiyadi, Sumiyadi; S. Damaianti, Vismaia (Universitas Hamzanwadi, 2024)
The purpose of this study is to determine the effect of using modules containing sasambo local wisdom on the ability to write narrative texts. The research method used is a quasi experiment. The experimental design used is before-after. The subjects of this study were 36 students. The instrument used is a portfolio sheet as an aspect value of students' narrative writing skills. The collected data were analyzed using correlated t-test tests. The result found was that students' ability to write narrative texts increased after using modules containing sasambo local wisdom. For these findings to be more useful for future researchers and teachers, modules containing sasambo local wisdom should be optimized in their use and development.